Kesehatan Lingkungan: Keberagaman Umat Beragama dalam Program Eco Bhinneka Muhammadiyah di Kota Ternate, Maluku Utara - Syahril, Fadila; Purnamawati , Dewi (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
This study examines the diversity of religious communities run by Eco Bhinneka Muhammadiyah in Ternate City, North Maluku, in the context of environmental health. This program integrates environmental conservation with interfaith harmony through various collaborative activities such as workshops, interfaith dialogues, and environmental clean-up actions. Qualitative research methods were used with data collection through interviews and document studies. The results show that interfaith collaboration is effective in building awareness of environmental conservation and social harmony, which has a positive impact on community environmental health. This program has also succeeded in building a new culture that prioritizes the values ​​of compassion and respect between religious communities and nature conservation in Ternate City.